Effect of a Low-Carbohydrate High-Fat Diet and a Single Bout of Exercise on Glucose Tolerance, Lipid Profile and Endothelial Function in Normal Weight Young Healthy Females - Valsdottir, Thorhildur Ditta; Henriksen, Christine; Odden, Nancy; Nellemann, Birgitte; Jeppesen, Per B.; Hisdal, Jonny; Westerberg, Ane C.; Jensen, Jørgen (Frontiers in Physiology, 2019)
Low-carbohydrate-high-fat (LCHF) diets are efficient for weight loss, and are also used by healthy people to maintain bodyweight. The main aim of this study was to investigate the effect of three-week energy-balanced LCHF-diet, with >75 percentage energy (E%) from fat, on glucose tolerance and lipid profile in normal weight, young, healthy women. The second aim of the study was to investigate if a bout of exercise would prevent any negative effect of LCHF-diet on glucose tolerance. Seventeen females participated, age 23.5 ± 0.5 years; body mass index 21.0 ± 0.4 kg/m2, with a mean dietary intake of 78 ± 1 E% fat, 19 ± 1 E% protein and 3 ± 0 E% carbohydrates. Measurements were performed at baseline and post-intervention. Fasting glucose decreased from 4.7 ± 0.1 to 4.4 mmol/L (p < 0.001) during the dietary intervention whereas fasting insulin was unaffected. Glucose area under the curve (AUC) and insulin AUC did not change during an OGTT after the intervention. Before the intervention, a bout of aerobic exercise reduced fasting glucose (4.4 ± 0.1 mmol/L, p < 0.001) and glucose AUC (739 ± 41 to 661 ± 25, p = 0.008) during OGTT the following morning. After the intervention, exercise did not reduce fasting glucose the following morning, and glucose AUC during an OGTT increased compared to the day before (789 ± 43 to 889 ± 40 mmol/L120min-1, p = 0.001). AUC for insulin was unaffected. The dietary intervention increased total cholesterol (p < 0.001), low-density lipoprotein (p ≤ 0.001), high-density lipoprotein (p = 0.011), triglycerides (p = 0.035), and free fatty acids (p = 0.021). In conclusion, three-week LCHF-diet reduced fasting glucose, while glucose tolerance was unaffected. A bout of exercise post-intervention did not decrease AUC glucose as it did at baseline. Total cholesterol increased, mainly due to increments in low-density lipoprotein. LCHF-diets should be further evaluated and carefully considered for healthy individuals.